2011
DOI: 10.1007/s10151-011-0684-6
|View full text |Cite
|
Sign up to set email alerts
|

Does pilonidal abscess heal quicker with off-midline incision and drainage?

Abstract: Pilonidal abscess should be drained away from the midline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 18 publications
1
13
0
2
Order By: Relevance
“…This finding is consistent with previous studies. 17,19 Webb and Wysocki 17 found that metronidazole was omitted in most antibiotic regimens used in the management of acute pilonidal disease in their institute, similar to our findings.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous studies. 17,19 Webb and Wysocki 17 found that metronidazole was omitted in most antibiotic regimens used in the management of acute pilonidal disease in their institute, similar to our findings.…”
supporting
confidence: 93%
“…17 Patients with larger abscesses are probably more likely to require repeated aspiration. However, the definition of large abscess in this study (15-40 mL) is arbitrary, and the follow-up should be tailored to each patient based on clinical assessment.…”
mentioning
confidence: 99%
“…The conservative methods such as phenol injection, laser epilation, and shaving are used in the early stages of PSD with different success rates [8][9][10]. Surgical methods including primary closure, marsupialization, the Limberg flap, and cleft closure [11][12][13][14][15] have also been performed for treating PSD; however, there is no current agreement as to what the ideal treatment is. The preferred operation for PSD should be simple, cost-effective, and associated with minimal pain and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a relationship between wound infection and recurrence rate has been demonstrated . Bacteria that infect PS are reportedly sensitive to metronidazole because of the predominance of anaerobic bacteria . In a study with 50 patients who underwent excision of a PS and midline closure, Chaudhuri et al compared single‐dose antibiotic treatment with solely metronidazole with cefuroxime plus metronidazole followed by amoxicillin/clavulanic acid for 5 days and found the latter treatment to be superior .…”
Section: Discussionmentioning
confidence: 99%